Implementation of Disability-Friendly Population Services: A Model for Inclusive and Accessible - Az Zahra Azizah Nur Aulia; Tukiman Tukiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study focuses on the implementation of the population document facilitation service program (NASI UDUK PEDAS) at the Population and Civil Registration Office of Trenggalek Regency in an effort to maintain orderly administration in various vulnerable groups. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews with key informants, including Disdukcapil staff and disability companions, as well as document analysis and direct observation. Data sources include primary and secondary data collected through observation, documentation, and interviews. Data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions. The results show that the Population and Civil Registration Office of Trenggalek Regency has implemented the NASI UDUK PEDAS program to realize orderly administration, which focuses on outreach services for people with disabilities. However, implementation in the field faces several challenges such as the lack of standard operating procedures, obstacles from families, program consistency, budget efficiency, and geographical conditions. From this analysis, the main recommendations given include creating standard operating procedures, providing more routine socialization, and creating a consistent service schedule every month.